Occupational Health Risks in Solid Waste Management: A Literature Review: Assessing Occupational Health Risks in Solid Waste Management Practices (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This is a literature review paper based on articles on occupational health risks of workers involved in municipal solid waste management. It looks into the environmental health problems associated with solid waste management, health effects on workers near hazardous waste landfill sites, musculoskeletal disorders arising out of handling municipal solid wastes etc. It also looks into the cost (loss) and magnitude of occupational health in solid waste management. Lastly the paper provides some recommendations for safety and suitability of municipal solid waste management practices, improving work organization and availability of personal protection equipment.